OPTIMALISASI MANAJEMEN PENGEMBANGAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DAN PROFIL PELAJAR RAHMATAN LIL ALAMIN DI MADRASAH - Yulianto, Haries; Thoha, Mohammad (re-JIEM (Research Journal of Islamic Education Management), 2025)
Character development through project-based activities is a central focus in the implementation of value-based education. The Project for Strengthening the Profile of Pancasila Students and the Profile of Students with Compassion for the Universe is applied in Islamic schools as a contextual learning model that internalizes national and religious values. This study aims to examine the management of project development in Madrasah Tsanawiyah Negeri 2 Pamekasan, focusing on the planning, implementation, evaluation, achievements, challenges, and optimization strategies. The research employed a qualitative descriptive approach using participatory observation, in-depth interviews, and document analysis. Informants included the head of the madrasah, project coordinators, project teachers, students, and education staff. The findings show that the management of project development was carried out collaboratively, flexibly, and value-based, involving active participation of all school components. The implementation phase encouraged experiential learning that effectively fostered students' character, social responsibility, and critical thinking skills. Evaluation was conducted reflectively and authentically, emphasizing process and student engagement rather than mere outcomes. The main challenges identified were limited time, logistical constraints, and varying capacities among facilitators. Optimization strategies included teacher training, schedule integration, improved evaluation tools, external collaboration, and thorough documentation. This study provides practical insights for other Islamic educational institutions in designing and managing value-based projects in a structured and sustainable manner.